Heterogeneity in coverage for measles and varicella vaccination in toddlers - analysis of factors influencing parental acceptance - Christine Hagemann; Andrea Streng; Alexander Kraemer; Johannes G. Liese (BMC, 2017)
Abstract Background In 2004, routine varicella vaccination was introduced in Germany for children aged 11-14 months. Routine measles vaccination had already been introduced in 1973 for the same age group, but coverage is still too low (<95%) in some areas to eliminate measles. The present study assessed varicella and measles vaccination coverage and determinants of parental acceptance in two study regions, situated in Northern and Southern Bavaria (Germany). Methods From 2009 to 2011, annual cross-sectional parent surveys were performed on random samples of 600 children aged 18-36 months in the Bavarian regions of both Munich and Würzburg. Logistic regression models were used to identify factors associated with varicella and measles vaccination. Results In 2009, 2010 and 2011, vaccination coverage was lower in Munich than in Würzburg, for both varicella (Munich 53%, 67%, 69% vs. Würzburg 72%, 81%, 83%) and for measles (Munich 88%, 89%, 91% vs. Würzburg 92%, 93%, 95%). Recommendation by the physician was the main independent factor associated with varicella vaccination in both regions (adjusted odd ratios (OR) with 95% confidence interval (CI): Munich OR 19.7, CI 13.6-28.6; Würzburg OR 34.7, CI 22.6-53.2). Attendance at a childcare unit was positively associated with a higher acceptance of varicella vaccination in Munich (OR 1.5, CI 1.1-2.2). Regarding measles vaccination, attendance at a childcare unit was positively associated in both regions (Munich OR 2.0; CI 1.3-3.0; Würzburg OR 1.8; CI 1.1-3.1), and a higher level of parental school education was negatively associated in Würzburg (OR 0.5, CI 0.3-0.9). Conclusions Vaccination rates differed between regions, with rates constantly higher in Würzburg. Within each region, vaccination rates were lower for varicella than for measles. Measles vaccination status was mainly dependent upon socio-demographic factors (attendance at a childcare unit, parental school education), whereas for the more recently introduced varicella vaccination recommendation by the physician had the strongest impact. Hence, different strategies are needed to further improve vaccination rates for both diseases.